2014
DOI: 10.1002/btpr.1900
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization for reverse micellar extraction of stem bromelain with a focus on back extraction

Abstract: In the current study, reverse micellar extraction (RME) for the purification of stem bromelain was successfully achieved using the sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/isooctane system. A maximum forward extraction efficiency of 58.0% was obtained at 100 mM AOT concentration, aqueous phase pH of 8.0 and 0.2 M NaCl. Back extraction studies on altering stripping phase pH and KCl concentration, addition of counter-ion and iso-propyl alcohol (IPA) and mechanical agitation with glass beads indicated that I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The model lack of fit was shown to be insignificant (p > 0.05) with an F value of 0.55. The lack of fit measures the failure of the model to represent data in the experimental domain at points that are not included in the model . Table depicts the model regression co‐efficient that indicates the effect of variables on the hIFN‐γ production.…”
Section: Resultsmentioning
confidence: 99%
“…The model lack of fit was shown to be insignificant (p > 0.05) with an F value of 0.55. The lack of fit measures the failure of the model to represent data in the experimental domain at points that are not included in the model . Table depicts the model regression co‐efficient that indicates the effect of variables on the hIFN‐γ production.…”
Section: Resultsmentioning
confidence: 99%
“…The use of affinity based reverse micellar extraction and separation technique to extract and purify bromelain from pineapple waste yielded purification of 12.32 fold with an activity recovery of 185.6 % (Kumar et al 2011). Moreover the process optimization studies for RMS had been reported (Fileti et al 2009;Dhaneshwar 2014) and both the batch and continuous extraction of bromelain from pineapple juice by under optimized conditions was also studied (Fileti et al 2007). A neutral model developed for bromelain extraction from pineapple juice by RMS under optimized conditions gave 4.96 purification factor with productivity of 1.29 ml/min (Fileti et al 2009).…”
Section: Reverse Micellar Systemmentioning
confidence: 99%